Manajemen Strategi Fundraising dalam Meningkatkan Pendapatan Dana Zakat Pada Badan Amil Zakat Nasional (BAZNAS) Kota Probolinggo - Islahiyah Okta Novita Sari; Nasirudin Al Ahsani (Maddah: Journal of Advanced Da'wah Management Research, 2022)
According to the potential zakat data in Indonesia, as reported by TEMPO.CO Jakarta, the National Zakat Agency (BAZNAS) states that the potential zakat in Indonesia reaches Rp 327 trillion per year. The potential zakat has not been maximized in Indonesia, therefore an optimal fundraising strategy management is needed to maximize the potential zakat in Probolinggo City. The focus of this thesis research is: 1) How is the fundraising strategy management of BAZNAS Probolinggo City? 2) How is the fundraising strategy management related to the increase in zakat funds carried out by BAZNAS Probolinggo City? This research aims to identify and describe the fundraising strategy management and the increase in zakat funds at BAZNAS Probolinggo City. This research uses a qualitative research approach with a field research type. The research subjects were determined using purposive sampling. The data analysis used in this research includes data collection, data reduction, data presentation, and conclusion drawing. Meanwhile, to test the data validity, the researcher used method triangulation and source triangulation. The results of the research are: 1) The fundraising strategy management conducted by BAZNAS Probolinggo City uses two fundraising methods, namely direct fundraising and indirect fundraising. 2) With the fundraising strategy management and efforts carried out by BAZNAS Probolinggo City, the zakat funds have increased from 2019 to 2021.